Theorizing the Religious Habitus in the Context of Conversion to Islam among Polish Women of Catholic Background. (16th March 2021) - Krotofil, Joanna; Piela, Anna; Górak-Sosnowska, Katarzyna; Abdallah-Krzepkowska, Beata
Abstract: This article explores the conversion processes of Polish women of Catholic background to Islam. Data from participant observation of mosque-based, women-only weekend gatherings for converts and in-depth interviews with 29 Polish female converts to Islam are presented to illustrate the dialectic between the persistence and transformation of religious habitus. Our analysis demonstrates that in the conversion process, Catholic habitus remains pervasive, and shapes converts' engagement with the new religion; however, some elements of it become reflexive and change. We make a case for extending the discussion on habitus transformation by drawing attention to what we term a "translation" of religious beliefs and practices. Women in our study translate the system of Islamic practices and beliefs into a specific Catholic logic that is more intelligible to them and, in the process, recognize some of the power dynamics inherent in the religious field.